Do toll-free highways foster firm formation and employment growth? Results from a quasi-natural experiment - David B. Audretsch; Dirk Dohse; Jo\~ao Pereira dos Santos (Kiel Institute for the World Economy (IfW), 2017)
The paper studies the impact of a switch from free to charged highway provision on firm numbers and private sector employment in a cross-section of Portuguese municipalities. It exploits the fact that highway tolls in Portugal were unexpectedly raised in reaction to the financial crisis to establish causality. Results from a difference-in-differences analysis indicate a significantly negative effect of highway tolls on number of firms and employment in treated municipalities vis-à-vis the control group. We also find negative effects of tolls in municipalities not directly traversed by the treated highways, with larger firms and manufacturing firms being most strongly affected.
Keywords: R48; L25; R12; 330; infrastructure provision; regional economic development; quasi-natural experiment